(untitled) (Clinics, 2021)
OBJECTIVES: This study aims to compare the clinical efficacy of an integrated approach to prevent and treat the recurrence of moderate-to-severe intrauterine adhesions (IUA) after hysteroscopic transcervical resection of adhesion (TCRA). METHODS: The study included a total of 70 patients with moderate-to-severe IUAs who underwent TCRA. Patients were randomly divided into two groups: treatment group (n=35) and control group n=35). In the treatment group, patients underwent balloon uterine stent placement and artificial cycle as well as received intrauterine perfusion of Danshen injection and oral Chinese medicine. In the control group, patients underwent balloon uterine stent placement and artificial cycle as well as received hyaluronic acid sodium and intrauterine device (IUD). Follow-up was performed after treatment of uterine cavity, menstruation and pregnancy. RESULTS: After 3 months of treatment, we observed a significantly lower rate of intrauterine re-adhesion (45.71% versus 77.14%, p=0.044) and significantly higher clinical efficiency (82.86% versus 77.14%, p=0.025) in the treatment group than those in the control group. After 6 months of treatment, we observed a significantly higher clinical efficiency in the treatment group than that in the control group (88.57% versus 68.57%, p=0.039). During the follow-up period, the pregnancy rate was 45.71% and 37.14% in the treatment group and control group, respectively, although the difference was not statistically significant (p=0.628). CONCLUSIONS: After surgical management of IUA, the integrated treatment combining a uterus stent placement and artificial cycle with Danshen injection and oral Chinese medicine can improve the condition of menstruation, and prevent and treat recurrence of IUA.